2016
DOI: 10.1002/brb3.524
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms associated with concerns about falling in Parkinson's disease

Abstract: BackgroundConcerns about falling, a construct related to fear of falling, is increased in people with Parkinson's disease (PD) and is recognized as a barrier for exercise, negatively affecting health‐related quality of life and participation.AimTo investigate modifiable factors associated with concerns about falling in elderly with mild‐to‐moderate PD.MethodsEighty‐nine elderly (39 females, mean age 73 years) with mild‐to‐moderate PD were recruited. Concerns about falling were assessed with the Falls Efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
3
22
0
1
Order By: Relevance
“…In our study, experiences of FOF were described by men as well as women, and by those with and without a history of falls. This supports previous findings which showed that gender and experiences of falls are not independently associated with FOF in people with PD [ 2 , 4 , 10 , 11 , 13 ], which is in contrast to studies that involve elderly persons without PD [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, experiences of FOF were described by men as well as women, and by those with and without a history of falls. This supports previous findings which showed that gender and experiences of falls are not independently associated with FOF in people with PD [ 2 , 4 , 10 , 11 , 13 ], which is in contrast to studies that involve elderly persons without PD [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…FOF is a predictor of future falls and near falls already in mild PD [ 6 ], and is negatively associated with participation and health-related as well as overall quality of life [ 7 9 ]. Studies that used multivariable regression analyses to identify explanatory factors of FOF have shown that PD-related disabilities such as walking difficulties, need of help in activities of daily living, motor symptoms, orthostatism, poor functional balance and fatigue are significantly associated with FOF in people with PD [ 2 , 4 , 8 , 10 13 ]. Female gender and a history of falls have been shown to be significant and independently explanatory factors of FOF in the overall elderly population [ 14 ] but not in people with PD [ 2 , 4 , 10 , 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation was that we did not investigate if the participants had psychological symptoms like depression, that may have negatively affected how they coped with reduced balance. Our earlier research have shown a relation between fear of falling and depressive symptoms [58]. To increase credibility, the analyzed material was peer-debriefed by other authors (HJ, EF and BE) at several occasions [38].…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier research have shown a relation between fear of falling and depressive symptoms. 58 To increase credibility, the analyzed material was peer-debriefed by other authors (HJ, EF and BE) at several occasions. 38 There was an equal amount of men and women included in the study.…”
Section: Discussionmentioning
confidence: 99%